Analytical Study of Organic Herbal And Animal Medicines In Al-Fath Manuscript Of Medication And Its Problems " (Journal of Human Sciences, 2023)
This paper examines and analyses herbal and animal medicines detailed in Al-Fath manuscript of medication; Based on the invaluable historical manuscripts as they are a source of information on pharmacology. Our new manuscript highlights hundreds of herbal and animal medicines in our country, detailing their prescriptions for many for diseases and clarifying their effects, alternatives and associated characteristics. The problem this research focuses on is that the herbal and animal medicines contained in Al-Fath manuscript were varied in their names, rich in content, available in local environment, and fighting diseases. This problem has therefore been associated with several questions, including: What are the herbal and animal medicines contained in the manipulator? Has their value expired? Or are they still valid today without side effects? Has the effectiveness of these medicines drawn the ire of Ottoman power in our country and where did they stand?                                                The importance and purpose of the subject of this research is to clarify the relationship between history and pharmacy and the history of medicine in our country, as well as revive the use of herbal and animal medicines treated for diseases associated with the local environment as part of our Islamic law in the Holy Quran and the Prophets' Sunnah and what aligns with them from the social inheritance in conjunction with the weakness of the law and the spread of expired medicines or their side effects while emphasizing on the importance of the development of medical and pharmaceutical technology. This research will therefore be focusing on analysing the Arabic and scientific names of herbs and animal medicines and knowing their therapeutic recipes for multiple diseases and their associated effects and problems. Then we will conclude the research with the findings, annexed to its recommendations and list of sources and references.